Structure-Activity relationship of 1-(Furan-2ylmethyl)Pyrrolidine-Based Stimulation-2 (ST2) inhibitors for treating graft versus host disease. (1st October 2022) - Yuan, Xinrui; Jiang, Hua; Fu, Denggang; Robida, Aaron; Rajanayake, Krishani; Yuan, Hebao; Wen, Bo; Sun, Duxin; Watch, Brennan T.; Chinnaswamy, Krishnapriya; Stuckey, Jeanne A.; Paczesny, Sophie; et al.
Graphical abstract: Abstract: An elevated plasma level of soluble ST2 (sST2) is a risk biomarker for graft-versus-host disease (GVHD) and death in patients receiving hematopoietic cell transplantation (HCT). sST2 functions as a trap for IL-33 and amplifies the pro-inflammatory type 1 and 17 response while suppressing the tolerogenic type 2 and regulatory T cells activation during GVHD development. We previously identified small-molecule ST2 inhibitors particularly iST2-1 that reduces plasma sST2 levels and improved survival in two animal models. Here, we reported the structure–activity relationship of the furanylmethylpyrrolidine-based ST2 inhibitors based on iST2-1. Based on the biochemical AlphaLISA assay, we improved the activity of iST2-1 by 6-fold (∼6 μM in IC50 values) in the inhibition of ST2/IL-33 and confirmed the activities of the compounds in a cellular reporter assay. To determine the inhibition of the alloreactivity in vitro, we used the mixed lymphocyte reaction assay to demonstrate that our ST2 inhibitors decreased CD4 + and CD8 + T cells proliferation and increased Treg population. The data presented in this work are critical to the development of ST2 inhibitors in future.